Pengaruh Disonansi Kognitif Terhadap Perilaku Plagiarisme Pada Mahasiswa - Indah Pangesti; Nugroho Arief S Setiawan; Citra Wahyuni (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2023)
Plagiarism is rife in academic activities. Where one of them is the justification of student perceptions of learning achievement. The purpose of this study was to determine the effect of cognitive dissonance on plagiarism behavior in students. This research intervention uses the theory of Adishesa & Prawiro (2020). This study replicated the intervention by controlling for the mindfulness variable through the â€œstop plagiarismâ€ poster and 10 items of knowledge about plagiarism from the University of Southern Mississippi. This study used a posttest only two group experimental design. The sampling technique in this study used convenience sampling and obtained 40 students who were then divided into two groups, namely, the experimental group I and the experimental group II. Data analysis techniques used the Mann Whitney test to determine differences in plagiarism scores in the two research groups. The results showed that there were differences in plagiarism scores in the two groups with the Z test = -4.996 and sig. (2-tailed) is 0.00 < 0.05. The results showed that in the experimental group I where participants were given freedom by working on essays at home, the experimental group I got a higher plagiarism score than the experimental group II. Keywords: cognitive dissonance ; plagiarism behaviour ; students